School tracking and development of cognitive skills - Tuomas Pekkarinen; Roope Uusitalo; Sari Kerr (Institute for the Study of Labor (IZA), 2009)
The Finnish comprehensive school reform replaced the old two-track school system with a uniform nine-year comprehensive school and significantly reduced the degree of heterogeneity in the Finnish primary and secondary education. We estimate the effect of this reform on the test scores in the Finnish Army Basic Skills test. The identification strategy relies on a differences-in-differences strategy and exploits the fact that the reform was implemented gradually across the country during a six-year period between 1972 and 1977. We find that the reform had a small positive effect on the verbal test scores but no effect on the mean performance in the arithmetic or logical reasoning tests. Still in all tests the reform improved the scores of students from families where parents had only basic education.
urn:nbn:de:101:1-20090327255
Keywords: H52; I21; 330; Education; school system; tracking; comprehensive school; test scores; Allgemeinbildende Schule; Bildungsreform; Schulauswahl; Kognition; Qualifikation; Absolventen; Finnland